The recognition by Costa Rica of the human right to drinking water and sanitation: Challenges in relation to the Sustainable Development Goals of the 2030 Agenda - Quirós Orozco, Paula (2025)
In September 2016, Costa Rica became the first country in the world, part of the United Nations System, to sign the National Pact for Sustainable Development. This Pact has 17 Objectives, with access to drinking water and sanitation being number 6 of them. This responsibility obliges the country to create investment plans, national and international inter-institutional collaboration, and implementation of public policies that guarantee full coverage of drinking water and sanitation services. However, inequality between rural and urban areas are the aspects that keep the country from meeting this goal.